PENGARUH LUAS PANEN PADI, PRODUKTIVITAS, JUMLAH PENDUDUK DAN CURAH HUJAN TERHADAP KETAHANAN PANGAN DI PROVINSI JAWA TENGAH - Polykarvos Nubun; Yuliawati Yuliawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
In Indonesia, food security is an important issue in meeting the needs and welfare of the community because it has a decisive impact on economic, social and political stability in Indonesia. This research aims to analysis the impact of paddy’s harvested area, rice’s productivity, populations, and rain intensity on food securities in 29 districts on Province of Central Java. The analysist consists of four  independent variables used secondary data (panel analysis) with cross-section on 29 districts in three years, from 2018 to 2020 (data time series). The tool of analysis used is the regression method (panel analysis) called fixed effect model (FEM), all of data is processed by Eviews 11 SV (x64). The result shows that paddy’s harvested area, rice’s productivity, populations, and rain intensity are significant to food securities. As partial shown of the variable 1) Paddy’s harvested doesn't have significant correlation to food securities and has positive correlation to food securities. 2) The productivity of rice has a significant and negative correlation to food securities. 3) The variable of populations has significant and negative correlation to food securities. 4) The Rain’s intensity doesn't have significant correlation and has positive correlation to food securities. The results of classic assumption-test indicates that the model of the regression (panel analysis) are independent from normalities, multicollinearities, autocorrelations, and heteroscedasticities.